Machine Translation and Specialized Texts: A Brief Overview Comparing GOOGLE TRANSLATE, DEEPL and CHATGPT - Sakareva, Ivanka (Yearbook of the Department of Foreign Languages and Cultures, 2024)
Machine translation (MT) is essential in an era of globalization and fast information exchange, especially for translating specialized texts like technical documentation, scientific papers, and legal documents, which are crucial for international collaboration and knowledge sharing. These texts present unique challenges due to their specific terminology, complex structures, and nuanced contexts. Effective MT tools such as Google Translate, DeepL and ChatGPT need to deal not only with language equivalence but also with content-specific complexities. Translating specialized texts, therefore, requires more than just linguistic skills; it necessitates domain-specific knowledge and an appreciation of the complex relationship between language, structure, and context (based on a personal experience of translating legal, technical and scientific texts). As MT technology progresses, driven by advances in computational linguistics and AI, it aims to produce translations that are both technically accurate and contextually nuanced, addressing the challenges posed by the complexity and variability of human language, thus improving global communication and understanding.